(untitled) (MAUSAM, 1974)
Average distribution of rainfall around the centre of monsoon depression in separate intervals of six hours in central India is presented and discussed in this paper. It is observed that the area around the first 100 km of the depression centre is generally free from intense rainfall activities. Heavy rainfall belt is mostly confined to the left forward quadrants of the depression field. Rainfall is almost widespread in these quadrants in the third and fourth six-hour intervals, reckoned with 03 GMT. Hourly intensities of rainfall greater than 50 mm/hr are, however, more frequent during the first 6-hr interval.